2007
DOI: 10.1093/ps/86.10.2144
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Canola Meal-Based Diets Supplemented with Exogenous Enzyme and Digestible Lysine on Performance, Digestibility, Carcass, and Immunity Responses of Broiler Chickens

Abstract: The response of broiler chickens to 2 levels of endo-1,4-beta xylanase and endo-1,3-beta glucanase combination (with and without), 3 levels of digestible Lys (0.8, 0.9, and 1.0%), and 2 levels of canola meal (CM; 20 and 30%) were evaluated in 2 x 3 x 2 factorial arrangement. A total of 2,448 male Hubbard broiler chicks were fed on practical mash diets having 2,750 kcal of ME.kg(-1) and 19.6% CP from 1 to 42 d of age. The BW gain was significantly reduced when 30% CM was added in the diets during 1 to 21 d. Fee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
37
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(42 citation statements)
references
References 39 publications
4
37
0
1
Order By: Relevance
“…Inclusion of CM at a level of 5, 10 and 20% of the diet with or without enzyme supplementation did not affect carcass traits. These results agreed with previous reports (Sariçiçek et al, 2005;Mushtaq et al, 2007). On the contrary, Kocher et al (2001) found that different CM levels did not affect dressing percentages, but enzyme supplementation appeared to increase dressing percentage.…”
Section: Carcass Traitssupporting
confidence: 93%
“…Inclusion of CM at a level of 5, 10 and 20% of the diet with or without enzyme supplementation did not affect carcass traits. These results agreed with previous reports (Sariçiçek et al, 2005;Mushtaq et al, 2007). On the contrary, Kocher et al (2001) found that different CM levels did not affect dressing percentages, but enzyme supplementation appeared to increase dressing percentage.…”
Section: Carcass Traitssupporting
confidence: 93%
“…In our study, diets containing 30, 20 and 10% FCM had 4.08, 2.72 and 1.36 lmol/g of glucosionolates, respectively. Generally, the level of glucosinolates in poultry diets should be less than 2.5 lmol/g to ensure optimum performance (Mushtaq et al 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Tripathi and Mishra (2007) suggested that younger animals are more sensitive to glucosinolates than older ones. The higher sensitivity of chicks to antinutritional factors of FCM in early stages of life may contributed to their physiological status where they are still in development phase for some physiological functions such as digestion and digestive enzyme activity (Pearson et al 1983;Nitsan et al 1991;Mushtaq et al 2007).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, in the current study, the enzyme complex increased the AME digestibility possibly due to: i) enough substrate for the enzyme; or ii) a complimentary effect between the three enzymes used. However, others studies have shown that a β-glucanase and xylanase cocktail in Canola meal-based diets have no pronounced effect on the growth performance or nutrient digestibility (Mushtaq et al, 2007). …”
Section: Discussionmentioning
confidence: 99%